Evaluation of Digital Literacy Competencies in Education Teachers Early Childhood Education Teachers - Istiqomah, I; Zulkarnaen, Z (Universitas Muhammadiyah Surakarta, 2023)
Teachers’ digital literacy equips children with the skills and confidence to confront increasingly digitised challenges. This study seeks to provide a comprehensive understanding of the digital literacy competencies of early childhood education teachers. The research employs a descriptive qualitative method, utilising single or multiple case studies. Data collection involves interviews and observations of five Aisyiyah Bolon 1 Colomadu Kindergarten teachers. The findings reveal a need for enhanced digital literacy competencies among early childhood education teachers, particularly in leveraging technological devices for optimised learning experiences and the holistic development of young learners.